2019
DOI: 10.1073/pnas.1819309116
|View full text |Cite
|
Sign up to set email alerts
|

Switch-like activation of Bruton’s tyrosine kinase by membrane-mediated dimerization

Abstract: The transformation of molecular binding events into cellular decisions is the basis of most biological signal transduction. A fundamental challenge faced by these systems is that reliance on protein-ligand chemical affinities alone generally results in poor sensitivity to ligand concentration, endangering the system to error. Here, we examine the lipid-binding pleckstrin homology and Tec homology (PH-TH) module of Bruton's tyrosine kinase (Btk). Using fluorescence correlation spectroscopy (FCS) and membranebin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
93
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(111 citation statements)
references
References 53 publications
(74 reference statements)
10
93
0
Order By: Relevance
“…There are five structural domains in BTK (figure 1a), each of which has its own activation mechanism, and then jointly form the overall activation process of BTK. To date, many studies have explored to some extent the activation mechanism of different BTK domains [15,23,[32][33][34][35][36][37]. For example, some studies have shown PH dimerization [34,38], which could mediate the dimerization of the catalytic region of BTK [23], and that the A-loop may be associated with kinase domain dimerization [39].…”
Section: Discussionmentioning
confidence: 99%
“…There are five structural domains in BTK (figure 1a), each of which has its own activation mechanism, and then jointly form the overall activation process of BTK. To date, many studies have explored to some extent the activation mechanism of different BTK domains [15,23,[32][33][34][35][36][37]. For example, some studies have shown PH dimerization [34,38], which could mediate the dimerization of the catalytic region of BTK [23], and that the A-loop may be associated with kinase domain dimerization [39].…”
Section: Discussionmentioning
confidence: 99%
“…Pose 1 ( Figure 4 ) involves specific contacts between R133 and Y134 in the PHTH domain and the N-lobe of the kinase domain. Importantly, this crystallographically determined structure shows the PHTH domain adopting the “Saraste dimer” ( Hyvönen and Saraste, 1997 ), a structure that has been associated with binding of the BTK PHTH domain to the plasma membrane following production of PIP 3 from PIP 2 by PI3K ( Chung et al, 2019 ). Molecular dynamics simulations suggest that the BTK PHTH Saraste dimer is stabilized at the membrane by binding multiple PIP 3 lipids and mutations that are known to have disease relevance destabilized the dimer interface ( Wang et al, 2019 ).…”
Section: A Defining Feature Of Btk and The Tec Family Kinases The Phtmentioning
confidence: 98%
“…Molecular dynamics simulations suggest that the BTK PHTH Saraste dimer is stabilized at the membrane by binding multiple PIP 3 lipids and mutations that are known to have disease relevance destabilized the dimer interface ( Wang et al, 2019 ). Furthermore, elegant studies using supported lipid bilayers provide evidence that the peripheral site originally identified in the crystal structure of the BTK PH domain bound to IP 6 ( Wang et al, 2015 ) stabilizes membrane association ( Chung et al, 2019 ). This requirement for the occupancy of both PIP 3 sites for activation of BTK suggests that the PH domain is sensitive to the concentration of PIP 3 in the membrane.…”
Section: A Defining Feature Of Btk and The Tec Family Kinases The Phtmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, SLBs have been demonstrated in its usefulness in many works examining molecular interactions on membrane surfaces. Two such examples are K-Ras4B GTPase ( 25 ) and the pleckstrin homology (PH) domain of Bruton’s tyrosine kinase (Btk) in their dimerization behavior ( 26 ). Homodimerization is perhaps the simplest possible protein-protein interaction and is ubiquitous in signal transduction.…”
Section: Introductionmentioning
confidence: 99%